Variations in Semen Quality and Potential for Frozen Semen Production in Aceh Cattle - Sophian, E.; Said, S.; Setiadi, M. A.; Arifiantini, R. I. (Tropical Animal Science Journal, 2025)
The quality of fresh and frozen semen as well as the potential to produce frozen semen, vary considerably between individual animals and cattle breeds. This study aimed to analyze the quality of fresh and frozen semen in Aceh cattle and calculate the potential production of frozen semen in Aceh bulls over 1 year. This study used primary data on the quality of fresh and frozen semen from five Aceh cattle and obtained secondary data from artificial insemination centers in Lembang and Singosari in 2022. Semen samples were collected weekly, and the quality of fresh and frozen semen samples were evaluated. The data were analyzed using a one-way analysis of variance at 95% significance level, followed by Tukey’s test. The results revealed differences in semen volume and pH. Based on microscopic characteristics, the semen samples from different bulls exhibited no discernible differences in mass movement, sperm motility, viability, morphology, and plasma membrane integrity, except for sperm concentration and acrosomal integrity. Bull 211605 exhibited the highest sperm concentration. Furthermore, the frozen semen samples from Aceh cattle showed no significant differences in viability, plasma membrane integrity, morphology, and acrosomal integrity. The total sperm motility of bull 211710 was higher than that of the other bulls. The highest progressive motility was observed in bulls 211710 and 211605, and the highest intact DNA was detected in bulls 211710 and 211605. The results of this study demonstrated that the quality of fresh and frozen semen in Aceh cattle is distinct, and the potential frozen semen production of Aceh cattle is estimated to range from 3,382 ± 1810 to 11,399 ± 2658 straws/year.